Understanding the leaching behavior of inorganic polymers made of iron rich slags. (20th November 2019) - Giels, Michiel; Iacobescu, Remus Ion; Cappuyns, Valérie; Pontikes, Yiannis; Elsen, Jan
Abstract: This study investigates the leaching of main and trace elements from inorganic polymers made with an iron rich, fumed, > 90% amorphous slag. Different inorganic polymer binders were synthesized, varying the amount of the activating solution and the silica over sodium oxide ratio from 1.6, to 1.8, to 2.0, with constant water content of ±63%. Cascade and column leaching tests were performed in combination with geochemical speciation modeling (Visual MINTEQ) with the aim to understand the speciation of the elements in the inorganic polymer and their leaching behaviour as a function of pH. This would allow to identify the elements which would be the major issue with respect to leaching when the slag will be used in a construction material. The formed inorganic polymer was able to immobilize cationic elements such as barium, copper, magnesium, manganese, and zinc, in the pH range 7–12.5 due to adsorption. Elements such as antimony, arsenic, phosphorus, molybdenum, and vanadium were easily leached out in column and cascade leaching tests, because they most likely occurred as anions in the pore solution. Lead, chromium, and titanium were immobilized in the binder or in crystalline phases in the pH range 3.5–12.5. The study shows that there are multiple factors that affect leaching, the most important of which is shown to be the nature (cationic or anionic) of the elements and the morphology of the matrix. Anions that are present as trace elements (<0.1 wt%) can pose a potential threat in valorising these slags and actions should be taken, either at the metallurgical process itself or downstream, at the synthesis of the inorganic polymers. On the other hand, the results for the cationic species suggest that they are effectively immobilised in most of the cases and for a wide pH range. Graphical abstract: Image 103337 Highlights: Barium, copper, magnesium, manganese and zinc are immobilized due to adsorption. Antimony, arsenic, phosphorus, molybdenum, and vanadium are mobilized as anions. Chromium, lead and titanium are immobilized in the binder or in crystalline phases. Trace elements (<0.1 wt%) can pose a potential treat in valorizing these slags.